Activities of the summer party of the 20th Japanese Antarctic Research Expedition in 1978-1979 - Yoshio Yoshida (National Institute of Polar Research, 1983)
Forty-four men of the 20th Japanese Antarctic Research Expedition (JARE-20) left Tokyo for Syowa Station on November 25,1978 aboard icebreaker FUJI to carry out scientific observation. Emphasis was laid on two 3-year projects : the POLEX-South and the integrated earth sciences programs which started in 1979. Scientific observations in the summer season were oceanographic observations along a cruise track and during mooring in the fast ice area near Syowa Station, deep seismic sounding of the earth's crust, and geological and geodetic surveys of the ice-free Kasumi Rock. Seven Australian drifting buoys for the First GARP Global Experiment were deployed between 39°S, 109°E and 62°S, 85°E. At Syowa Station construction of the basement of two-storied summer quarters and improvement of several observation huts and telecommunication facilities were carried out. An inland traverse to and from Mizuho Station was accomplished and a 30-m meteorological observation tower was built at Mizuho Station. A live telecast from Syowa Station to Japan was done by the Nippon Hoso Kyokai team from January 28 to February 3,1979,supported by JARE-19,-20 and the crew of FUJI. Eleven men consisted of news reporters, cameramen and technicians connected with JARE-20 for the telecast. Twelve men of the summer party returned to Tokyo on April 20,1979.